2012
DOI: 10.1177/000313481207800113
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Complex Liver Trauma: A Single Liver Transplant Center Experience

Abstract: Complex liver trauma often presents major diagnostic and management problems. Current operative management is mainly centered on packing, damage control, and early utilization of interventional radiology for angiography and embolization. In this retrospective observational study of patients admitted to the Mediterranean Institute for Transplantation and Advanced Specialized Therapies, Palermo, Italy, from 1999 to 2010, we included patients that underwent hepatic resection for complex liver injuries (grade I to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Postoperative prolonged hemorrhage can be associated with coagulopathy [ 5 , 10 , 27 , 29 ]. While blood transfusion is necessary because of massive bleeding in trauma, it carries many complications [ 29 , 30 ].…”
Section: Discussonmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative prolonged hemorrhage can be associated with coagulopathy [ 5 , 10 , 27 , 29 ]. While blood transfusion is necessary because of massive bleeding in trauma, it carries many complications [ 29 , 30 ].…”
Section: Discussonmentioning
confidence: 99%
“…Our study shows that non-survivors had higher AAST grade of injury, higher AST and ALT level, significant hypotension, higher ISS score and lower GCS on arrival; and significalntly more RBC units transfusions within the first 24 h. Early liver injury-related death is typically secondary to uncontrolled bleeding (20–60 %), which is worsened with attendant coagulopathy, whereas late mortality is usually secondary to multiorgan failure (MOF), Acute Respiratory Distress Syndrom (ARDS) in 27(32.1 %), and Multiple Organ Dysfunction Syndrome (MODS) [ 6 , 29 31 ]. Previous studies have shown that increased risk of ARDS and MODS has been associated with massive transfusion, which can itself contribute to coagulopathy [ 30 ]. In blunt liver trauma mortality also appears to be higher in older patients, those with higher grade injuries, and those with hemodynamic instability on presentation [ 29 31 ].…”
Section: Discussonmentioning
confidence: 99%
“…The primary search identified 29 articles published between January 2000 and June 2014 that were screened (Figure 1) (10,11). A further 17 articles were excluded: 9 that amalgamated penetrating and blunt hepatic injury (4,(12)(13)(14)(15)(16)(17)(18)(19), 6 where the demographics characteristics and outcome of grade III to V blunt hepatic injury was not comprehensively depicted (20)(21)(22)(23)(24), and 2 included exclusively patients with juxtahepatic venous injury (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…The advent of the acute care surgery fellowship might help. Trauma surgeons also need to consider collaborating more closely with colleagues who have real experience in liver surgery, including those in transplantation [26] . Involving the transplant team at an early stage in a patient’s course is important for another reason, namely, to help avoid long-term complications posttransplant.…”
Section: Discussionmentioning
confidence: 99%